Experimental investigation of the base flow from the nozzles with sudden expansion - Chaudhary, Zakir Ilahi; Shinde, Vilas B.; Bashir, Musavir; Khan, Sher Afghan (Research India Publications, 2015)
This paper presents the outcome of the experimental investigation conducted to control the base pressure for suddenly expanded flow for a fairly high area ratio of non-dimensional backward facing step height of 2.2. The Mach number range of the study were from 1.25 to 3.0 and the NPRs in the range from 3 to 11. The length-to-diameter ratio of the present study was varied from 1 to 10. It is seen that, the relief and L/D combination results in control effectiveness at various Mach numbers taking the base pressure above or below the value of the without case. This shows that the level of base pressure is sensitive to the combination of parameters under study. If base drag reduction is the aim, NPR 11 and L/D range from 10 to 5 seem to be the choice for that. If base suction enhancement is desired, Mach number in the range 2.5 to 3.0 and L/D 10 to 4 seem to be the choice.